Uma abordagem do estudo de sequências e séries numéricas na matemática do ensino médio - Silva Filho, Valdemiro Carlos dos Santos (Universidade Federal do Tocantins, 2021)
This research aims to study Sequences and Numerical Series through proposed activities for high school. Considering that Sequences and Numerical Series are contents covered in Basic Education, such as Arithmetic and Geometric progressions, activity proposals were developed to be performed by the teacher in the introduction of the Infinite Numerical Series content. Thus, we start from the problem that we can start the concept of infinite sums in high school for better student understanding, as a way to stimulate learning as suggested by the Educando Development Plan, for better teaching quality. In these ques tions, the research that best suited our project was the bibliography of an exploratory methodology, in which the consultation of materials such as magazines, dissertations and other sources, are paramount. During this work, we present the historical aspects in a succinct way about the Sequences and Numerical Series, as their appearance and progress in the mathematical environment, to their development. When deepening the study of this theme, we found the theoretical foundations necessary to propose the planned activi ties. We understand that these actions can be facilitating tools in the process of acquiring mathematical knowledge by the students, contributing to the development of logical rea soning, in addition to being possibly more attractive due to the suggested approach. We concluded the work considering our proposal to be more than satisfactory and could serve as a basis for further research and further research.